If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6(x-17)=42
We move all terms to the left:
6(x-17)-(42)=0
We multiply parentheses
6x-102-42=0
We add all the numbers together, and all the variables
6x-144=0
We move all terms containing x to the left, all other terms to the right
6x=144
x=144/6
x=24
| 4u+8=5u-8 | | a-√a=0 | | 3x-2x+4x=10 | | n2−63=0 | | 34+n+112=78-7 | | 1/3(2x-3)+4x=13 | | Y=5/7x+10 | | |6-2n|=4 | | 4k+16=3k+14 | | 4k-14=3k+21 | | 2/(x+8)=15/(3-2x) | | -275=-8(5x-6) | | 4x-11=-7 | | x+10=-x+6 | | 50=-16x^2+48x+64 | | 1/3x+3/5=x-1/9 | | 0.6x-2=x | | 6-(x+3)=4x | | 4x^2+6000x+3999936=0 | | X+4y=180° | | 4x^2+60x-6000=0 | | 4x^2+60x-336=0 | | 0.2x=3866.90 | | p=6p | | 4x^2+60x-240=0 | | p=6p=60 | | 3-5x+2x=2-2(1-x) | | 9(2x-7)=11x-126 | | 48+(x-48)+x=180 | | (x-48)+x=180-48 | | .65+.35y=1 | | 4610+.35y=1 |